Norway : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
This Selected Issues paper of Norway presents a cyclical indicator of fiscal policy at the general government level, and provides an updated assessment of the long-term fiscal position based on the future profile of the State Petroleum Fund (SPF). The study focuses on structural changes needed and prospects for privatization of state assets in the telecommunications and petroleum sectors. The paper analyzes the key issues in the Norwegian financial sector, outlines recent financial developments and banking soundness indicators, and also assesses the financial policy framework.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet